Surfactant Protein-A Function: Knowledge Gained From SP-A Knockout Mice - Depicolzuane, Lynnlee; Phelps, David S.; Floros, Joanna (Frontiers in Pediatrics, 2022)
Pulmonary surfactant proteins have many roles in surfactant- related functions and innate immunity. One of these proteins is the surfactant protein A (SP-A) that plays a role in both surfactant-related processes and host defense and is the focus in this review. SP-A interacts with the sentinel host defense cell in the alveolus, the alveolar macrophage (AM), to modulate its function and expression profile under various conditions, as well as other alveolar epithelial cells such as the Type II cell. Via these interactions, SP-A has an impact on the alveolar microenvironment. SP-A is also important for surfactant structure and function. Much of what is understood of the function of SP-A and its various roles in lung health has been learned from SP-A knockout (KO) mouse experiments, as reviewed here. A vast majority of this work has been done with infection models that are bacterial, viral, and fungal in nature. Other models have also been used, including those of bleomycin-induced lung injury and ozone-induced oxidative stress either alone or in combination with an infectious agent, bone marrow transplantation, and other. In addition, models investigating the effects of SP-A on surfactant components or surfactant structure have contributed important information. SP-A also appears to play a role in pathways involved in sex differences in response to infection and/or oxidative stress, as well as at baseline conditions. To date, this is the first review to provide a comprehensive report of the functions of SP-A as learned through KO mice.